Rare delayed cardiac tamponade in a pig after cardiac surgery. Issue 5 (3rd August 2022) - Li, Ke; Segura, Ana Maria; Sun, Junping; Chen, Qi; Cheng, Jie; Perin, Emerson C.; Elgalad, Abdelmotagaly
Abstract: Objective: Delayed cardiac tamponade, a life‐threatening complication of pericardial effusion in humans, has rarely been described in large animal models. We report here a pig with cardiac tamponade that developed 29 days after cardiac surgery. Study Design: Case report. Animals: One 45‐kg domestic pig. Methods: Open‐chest surgery was performed on a pig to induce chronic heart failure. At 15 days after surgery, the pig's breathing appeared laboured; induced heart failure was considered the cause. Routine heart failure medications were administered. Results: On day 28, the pig's status deteriorated. On day 29, echocardiography performed just before the pig's death showed a large pericardial effusion, mainly in the lateral and anterior walls of the right heart, with several fibre exudation bands. The right heart was severely compressed with an extremely small right ventricle. An emergency sternotomy was unsuccessful. Pathologic examination showed a severely thickened, fibrous pericardium. The pericardial sac was distended (up to 4.5 cm) and was full of dark brown, soft, friable material. Epicardial haemorrhage with a fresh, organised thrombus was noted in the pericardium. Conclusion: Delayed tamponade occurring at least 15 days after open‐chest surgery is easy to misdiagnose or overlook in large animal models where attention is often focused on primary pathological model changes. To decrease mortality in animal models, researchers should be aware of potential complications and use the same level of follow‐up monitoring of large animals as in clinical care. Abstract : In this report, we describe the development of delayed cardiac tamponade in a pig 29 days after cardiac surgery. This life‐threatening complication has rarely been described in large animal models and is easy to misdiagnose or overlook because attention is often focused on primary pathological model changes. To decrease mortality in animal models, researchers should be aware of potential complications and use the same level of follow‐up monitoring of large animals as in clinical care.